Stk40 links the pluripotency factor Oct4 to the Erk/MAPK pathway and controls extraembryonic endoderm differentiation - Li, Lingjie (National Academy of Sciences, 2010)
Self-renewal and differentiation of embryonic stem cells (ESCs) are controlled by intracellular transcriptional factors and extracellular factor-activated signaling pathways. Transcription factor Oct4 is a key player maintaining ESCs in an undifferentiated state, whereas the Erk/MAPK pathway is known to be important for ESC differentiation. However, the manner in which intracellular pluripotency factors modulate extracellular factor-activated signaling pathways in ESCs is not well understood. Here, we report identification of a target gene of Oct4, serine/threonine kinase 40 (Stk40), which is able to activate the Erk/MAPK pathway and induce extraembryonic–endoderm (ExEn) differentiation in mouse ESCs. Interestingly, cells overexpressing Stk40 exclusively contribute to the ExEn layer of chimeric embryos when injected into host blastocysts. In contrast, deletion of Stk40 in ESCs markedly reduces ExEn differentiation in vitro. Mechanistically, Stk40 interacts with Rcn2, which also activates Erk1/2 to induce ExEn specification in mouse ESCs. Moreover, Rcn2 proteins are specifically located in the cytoplasm of the ExEn layer of early mouse embryos. Importantly, knockdown of Rcn2 blocks Stk40-activated Erk1/2 and ESC differentiation. Therefore, our study establishes a link between the pluripotency factor Oct4 and the Erk/MAPK signaling pathway, and it uncovers cooperating signals in the Erk/MAPK activation that control ExEn differentiation.